Infantile spasms and early-onset progressive polycystic renal lesions associated with TSC2/PKD1 contiguous gene deletion syndrome. (March 2021) - Matsubara, Yoshie; Akamine, Satoshi; Chong, Pin Fee; Kawakami, Saori; Maehara, Kenji; Kaku, Yoshitsugu; Kurokawa, Mari; Morisada, Naoya; Iijima, Kazumoto; Kira, Ryutaro
Highlights: TSC2/PKD1 contiguous gene deletion syndrome is a rare cause of tuberous sclerosis. We report the case of infantile spasms with early-onset polycystic kidney lesions. Renal lesions can be detected in early infancy and show progressive enlargement.